Energy and nutrient intakes in relation to National Nutrition Recommendations in a Norwegian population-based sample: the Tromsø Study 2015–16 - Lundblad, Marie Wasmuth; Andersen, Lene Frost; Jacobsen, Bjarne Koster; Carlsen, Monica Hauger; Hjartåker, Anette; Grimsgaard, Sameline; Hopstock, Laila Arnesdatter (Food & Nutrition Research, 2019)
Introduction : According to the Global Burden of Disease project, unhealthy diet accounts for most of the disease burden in Norway. Current recommendations on nutrient intake in Norway reflect those published in the evidence-based Nordic Nutrition Recommendations from 2012 (NNR2012). Aim : To study energy and nutrient intakes and compliance with the NNR2012 among women and men in a population-based study. Methods : A total of 15,146 participants (aged 40–99 years) completed a validated food frequency questionnaire (261 questions on food items, meals, and beverages) in the seventh survey of the Tromsø Study in 2015–16; 11,425 participants were eligible for the current analysis. Nutrient intake was estimated by a food and nutrient calculation system at the University of Oslo, Norway. We compared energy, macronutrient, and micronutrient intakes with the NNR2012. Results : In total, 85% of the women and men were not in compliance with the maximum recommended intake of saturated fat, and 40 and 77% of women and men, respectively, were not in compliance with the lowest recommended intake of fiber. More than 30% of women and 25% of men had a relatively high probability of inadequate intake of vitamin D, and more than 10% of the men had a relatively high probability of inadequate intake of vitamin B6 and vitamin C. More than 20% of women and men had a high probability of excessive intake of niacin, and almost 40% of women had a high probability of excessive intake of vitamin A. Conclusion : Although most participants were in compliance with NNR2012, a large proportion of participants had higher intakes than maximum recommended for saturated fat, and lower than recommended for fiber and vitamin D.